PEMANFAATAN RUANG PUBLIK KOTA OLEH PKL DARI SUDUT PANDANG ARSITEKTUR EMPATI - Gandhi, Joses; Choandi, Mieke (Jurusan Arsitektur dan Perencanaan, 2024)
Indonesia's population growth increases rapidly every year, one of the causes is urbanization. However, the availability of job opportunities in the formal sector cannot keep up with rapid population growth. Therefore, the informal sector is the last option for residents and immigrants to avoid unemployment, and street vendors (PKL) are one of the informal sectors that have developed into an integral part of the life of city residents in housing, education, recreation and other living spaces. The development of street vendors in the city has increased significantly and brought benefits to the community, but there are also several things that are detrimental to local communities, such as the use of pedestrian paths as business places for selling. This has a negative impact on the aesthetics and cleanliness of the city environment. This research uses a qualitative descriptive method with data obtained through interviews and conducting literature studies. This research focuses on investigating the extent to which architecture can help improve the welfare and survival of informal sector workers, especially street vendors and find solutions to overcome problems that arise due to the presence of street vendors on a small and large scale. Apart from that, this research aims to eliminate the stigma about street vendors being dirty and only for the lower middle class community. It is hoped that the results of this research can help and improve the quality of life of the community, especially in urban areas, without damaging the aesthetics of urban public spaces. Keywords: informal sector; public space; quality of life; street food vendors; urbanization Abstrak Pertumbuhan penduduk Indonesia meningkat pesat tiap tahunnya, salah satu penyebabnya adalah urbanisasi. Namun, ketersediaan lapangan kerja di sektor formal tidak dapat mengimbangi pertumbuhan penduduk yang pesat. Oleh karena itu, sektor informal menjadi opsi terakhir bagi penduduk dan pendatang untuk menghindari pengangguran, dan pedagang kaki lima (PKL) termasuk salah satu sektor informal yang berkembang menjadi bagian integral dalam tata kehidupan warga kota di perumahan, pendidikan, rekreasi dan ruang kehidupan lainnya. Perkembangan PKL di kota meningkat signifikan dan membawa keuntungan bagi masyarakat, tetapi terdapat pula beberapa hal yang merugikan masyarakat lokal sekitar, seperti pemakaian jalur pejalan kaki menjadi tempat usaha untuk berjualan. Hal ini berdampak buruk terhadap estetika dan kebersihan dari lingkungan kota. Penelitian ini menggunakan metode deskriptif kualitatif dengan data yang didapat melalui wawancara dan melakukan studi pustaka. Penelitian ini berfokus untuk menginvestigasi sejauh mana arsitektur dapat membantu meningkatkan kesejahteraan dan kelangsungan hidup pekerja sektor informal, khususnya PKL dan menemukan solusi untuk mengatasi masalah yang timbul akibat kehadiran PKL dalam skala kecil maupun besar. Selain itu, penelitian ini bertujuan untuk menghilangkan stigma tentang PKL yang kotor dan hanya untuk memenuhi kebutuhan masyarakat menengah ke bawah saja. Diharapkan hasil penelitian ini dapat membantu dan meningkatkan kualitas hidup dari masyarakat terutama di perkotaan, tanpa merusak estetika dari ruang publik kota.